Polarization entanglement enabled by orthogonally stacked van der Waals NbOCl2 crystals - Qiangbing Guo; Yun-Kun Wu; Di Zhang; Qiuhong Zhang; Guang-Can Guo; Andrea Alù; Xi-Feng Ren; Cheng-Wei Qiu (Nature Communications)
Abstract Polarization entanglement holds significant importance for photonic quantum technologies. Recently emerging subwavelength nonlinear quantum light sources, e.g., GaP and LiNbO3 thin films, benefiting from the relaxed phase-matching constraints and volume confinement, have shown intriguing properties, such as high-dimensional hyperentanglement and robust entanglement anti-degradation. Van der Waals (vdW) NbOCl2 crystal, with strong optical nonlinearities, has emerged as a potential candidate for ultrathin quantum light sources. However, polarization entanglement is inaccessible in the NbOCl2 crystal due to its unfavorable nonlinear susceptibility tensor. Here, by leveraging the twist-stacking degree of freedom inherently in vdW systems, we showcase the preparation of polarization entanglement and quantum Bell states.